Geochemistry and mineralogy of contrasting supergene gold alteration zones, southern New Zealand. (October 2017) - Craw, Dave; Kerr, Gemma
Abstract: Supergene alteration of gold deposits has had important geochemical effects that changed the mineralogy and textures of near-surface exposures and can affect the economics of gold mines by enhancing gold liberation and increasing gold grades. This study links observed mineralogy with 655 water analyses from environments relevant to supergene processes in the Otago Schist goldfield of southern New Zealand, and these analyses are used as proxies for past supergene processes. There are two contrasting supergene alteration styles in otherwise identical host rocks and mineralisation zones in this area. Long-term groundwater alteration of sediments and underlying basement near to a regional unconformity developed progressively since the Cretaceous. This alteration has affected orogenic gold deposits exposed at the unconformity, and has resulted in supergene enrichment of gold with localised formation of centimetre scale gold nuggets. Alteration processes occurred under circumneutral pH conditions (pH 6–8.5), and was accompanied by extensive oxidation and clay alteration of basement rocks and sediments. Gold was mobilised as thiosulphate and bisulphide complexes and was reprecipitated by redox changes near the unconformity. The chemical processes of supergene enrichment were primarily abiotic, with minor bacterial facilitation of late stage gold mobility at the micron scale. In contrast, supergene alteration of eroding freshly-exposed mountain outcrops has occurred in the late Cenozoic without Au enrichment apart from liberation and minor particle size enhancement. The ambient pH of the associated waters was also circumneutral, but localised and temporary acidification (to pH ∼3) has occured on the metre scale or less in sulphidic outcrops. This supergene alteration was dominated by oxidation but some low redox minerals, senarmontite and secondary stibnite, have formed during the early stages of oxidation or subsequent reduction. Sulphide decomposition, with associated localised acidification and gold remobilisation was probably enhanced by bacterial processes in these exposed outcrops. Graphical abstract: Highlights: Micron scale primary gold is mobilised in surficial oxidation zones at circumneutral pH as sulphur complexes. Minor acidification occurs on oxidising primary sulphide mineral surfaces. Gold reprecipitation occurs via oxidation and reduction reactions to form coarser particles over decades in mountains. Gold remobilisation at a regional unconformity surface forms centimetre scale nuggets over millions of years. Bacterial activity facilitates short-term surface Au mobility, but not long-term Au mobility in deep groundwater.